University of Zimbabwe industrial attachment web-based supervision system - Mahoko, Abraham (Midlands State University, 2021)
University of Zimbabwe Industrial Attachment Web-based Supervision system was developed to computerize the processes involved in the work-related supervision system. The institution was using a manual system in the supervision of students on attachment which means students were manually submitting their logbooks in hand, supervision was done manually, and therefore time consuming. The main aim of this research was to come up with a computerized web-based supervision system that rectifies all the problems associated with the manual system that was being used. The data was gathered using three different research techniques to have enough knowledge about the manual system that was being used and to find out if the users were comfortable with a computerized one. Questionnaires, interviews and focus groups were used to have a rich research and possibly to reach different users. Additionally, to develop a user friendly and interactive web-based solution system, PHP programming integrated with some java scripts and HTML5 was used. The database was designed through the use of MySQL server since this database designing tool enables data to be stored, manipulated, edited, deleted and updated. The system was tested and successfully installed. The system was implemented using a pilot changeover approach to minimize risks of failure. The main system functionality is that, it allows three types of users, that is, students on attachment, work supervisors and academic supervisors to be registered on the platform. Work-related supervisor assigns tasks/duties to attachés online and view completed tasks, giving feedback, supervising students as well as assessing the performance of the students. Student can view assigned tasks and update them upon completion on a daily basis. Various measures such as user identification, user authentication and access control have been put in place in order to counteract unauthorized users from using the system. For more security features, the system can be further developed using Java programming language or using Android Programming Language and or IOS for easy access and convenience purposes.